EVALUASI PERLAKUAN EQUAL-CHANNEL ANGULAR PRESSING (ECAP) DENGAN RUTE Bc PADA BATANG TITANIUM (Ti-ROD) DENGAN ANALISIS DIFRAKSI SINAR-X - Ibrahim Purawiardi; I Nyoman Gede Putrayasa Astawa (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
In this study, commercial titanium rod was treated by equal-channel angular pressing (ECAP) with Bc route and two passes. This treatment was then evaluated by means of x-ray diffraction (XRD) analytical method. The evaluation was concentrated in crystal structure and residual lattice strain investigations. There were no significant crystal structure change before and after ECAPed. However, there were significant change in residual lattice strain after ECAPed. Before ECAPed, this titanium rod consisted of two lattice strains i.e. 0.0052 and 0.0009. After ECAPed, longitudinal lattice strain reduced from 0.0052 to 0.0036 after first pass and reduced again to 0.0025 after two passes. Meanwhile, shear lattice strain changed from 0.0009 to 0.0032 after first pass and was then annihilated after two passes. These results show that ECAP treatment can reduce and eliminate lattice strains on titanium rod. This study also shows that the reduction of lattice strains implicates to the increasing of its hardness value.